PENGARUH LINGKUNGAN KERJA DAN KESEJAHTERAAN KARYAWAN TERHADAP SEMANGAT KERJA KARYAWAN (STUDI PADA KANTOR PUSAT PT PERKEBUNAN NUSANTARA V PEKANBARU) - Zagoto, Try Samuel Hotman; ", Kasmiruddin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This study aims to determine the influence of situational leadership style and work motivation on employee job satisfaction (study at the headquarters of PT Perkebunan Nusantara V Pekanbaru). Work Environment as Variable (X1), Employee Welfare as Variable (X2) and Employee Morale as a variable (Y). The method in this research is quantitative with SPSS program, where the samples used are employees at the headquarters of PT Perkebunan Nusantara V Pekanbaru that is as much as 100 respondents. In accordance with opinion (Roscoe, 2009) that the appropriate size in the study is 30 to 500. That number can already represent the population. Technique of collecting data through questionnaire. The result of this research conclude that Work Environment variable and Employee Welfare have significant influence to Employee Morale at the headquarters of PT Perkebunan Nusantara V Pekanbaru Keywords: Work Environvent, Employee Morale